Driving Agricultural Productivity in Indonesia: The Impact of Digital Transformation and Regional Disparities - Sulfiana Sulfiana (Global Review of Tourism and Social Sciences, 2025)
This study examines the impact of digital transformation on agricultural productivity across Indonesia, focusing on the roles of digital infrastructure, technology adoption, farmer education, government support, and cost of technology. Using a multiple regression model with data from 380 respondents across key agricultural regions, the findings reveal that technology adoption and government support have the most substantial impacts on productivity. Digital infrastructure and education also play significant roles, while the cost of technology has a smaller yet positive effect. The study highlights regional disparities, with Java and Sumatra benefiting most from digital transformation, while regions like Maluku and Papua face challenges due to limited resources and infrastructure. These findings emphasize the need for integrated policies targeting infrastructure development, education, and affordability to ensure inclusive growth. This research contributes to the understanding of digital transformation in agriculture and provides actionable insights for sustainable agricultural development